Front Cover: Zinc Oxide Defect Microstructure and Surface Chemistry Derived from Oxidation of Metallic Zinc: Thin‐Film Transistor and Sensor Behavior of ZnO Films and Rods (Chem. Eur. J. 17/2021). Issue 17 (8th February 2021) - Hoffmann, Rudolf C.; Sanctis, Shawn; Liedke, Maciej O.; Butterling, Maik; Wagner, Andreas; Njel, Christian; Schneider, Jörg J.
Abstract : Detection of combined defect cluster sites in zinc oxide : Oxidation of plasma sputtered zinc generates zinc oxide films in which Doppler broadening positron annihilation spectroscopy (PAS) and positron annihilation life‐time studies (PALS) make it possible to detect oxygen vacancies (Vo) that are in close proximity to zinc vacancies (VZn). They form defect cluster sites acting as shallow acceptors reducing the overall electron conductivity. PAS and PALS is able to correlate semiconducting behavior and microstructure in ZnO thin film transistors. More information can be found in the Full Paper by J. J. Schneider et al. on page 5422 .